Periodontal health status in patients with periodontal disease: A descriptive study among Emirati population - Danavanthi Bangera; Krishnan Viswanathan; Jayadevan Sreedharan; Prabhu Natarajan (International Journal of Public Health Science (IJPHS), 2022)
Globally, around 10-15% of adults aged 21 to 50 years and around 30% of the elderly are diagnosed with severe periodontitis. About 20-50% of the population is affected with periodontal disease. However, there is a lack of actual national data in the UAE on oral health and periodontal health status. To determine the periodontal health status among the Emirati population aged 18 to 65 years. Periodontal health status of the patients with periodontitis was assessed by measuring plaque index; gingival index, clinical attachment loss (CAL) and community periodontal index treatment need (CPITN). All collected data were processed descriptively by presenting in numbers and percentages and analytically by cross-tabulation between variables. The majority of the patients (84%) had a mild level of clinical attachment loss and 54% had probing pocket depth of 3.5-5.5 mm. Moderate loss of clinical attachment was observed in 30.8% of patients with a medical history of diabetes mellitus and hypertension and 10.8% with no medical history. Most of the patients need non-surgical periodontal treatment that is scaling and root planning along with oral hygiene instructions and maintenance to reduce the progression of periodontal diseases.